Comparison of regional bond strength among different types of posts luted with different types of cement - Al-Jumaily, Ahmed A; Al-Azzawi, Haitham J (Journal of Baghdad College of Dentistry, 2014)
Background: This in vitro study was carried out to investigate the effect of post space regions (coronal, middle and apical), the effect of post types ( Manually Milled Zirconia post, Prefabricated Fiber post, prefabricated Zirconia post) and the type of cement used (GIC, self-adhesive resin cement) on the bond strength between the posts and root dentin by using push-out test.Material and methods: Forty eight mandibular premolars extracted for orthodontic reasons (single rooted) were instrumented with ProTaper system (hand use) and obturated with gutta percha for ProTaper using AH26® root canal sealer following the manufacturer instructions. After 24 hours, post space was prepared using Zirix and Glassix drills no.3 creating 8 mm depth post space. The prepared samples were randomly divided into three main groups (16 samples each) according to the type of post used (Group A. Manually Milled Zirconia post, Group B. Prefabricated Fiber post and Group C. Prefabricated Zirconia post) .each group was subdivided into two subgroups (each subgroup contains 8 samples) according to the type of cement used (subgroup A1.Manually Milled Zirconia post cemented with GIC, subgroup A2.Manually Milled Zirconia post cemented with Speed cem),( subgroup B1.Prefabricated Fiber post cemented with GIC, Group B2. Prefabricated Fiber post cemented with Speed cem) and (subgroup C1.Prefabricated Zirconia post cemented with GIC, subgroup C2. Prefabricated Zirconia post cemented with Speed cem), after cementation and incubation for 24hrs, at 37°c and 100% humidity. Each root was sectioned horizontally into 3 slices (2 mm in thickness) representing the coronal, middle and apical regions of the post space. Push out bond strength test was performed and measured using a universal testing machine (Tinius-Olsen) at across head speed of 0.5 mm/min.Results: The results showed that regarding the root region, the bond strength values increased significantly from apical to coronal region for all types of posts in both tested cements. For the effect of post type, the manually Milled Zirconia post cemented with the self-cured resin cement (Speed cem) showed higher bond strength values. For type of cement, the self-adhesive resin cement (Speed cem) showed higher bond strength values.Conclusions: the retention of post restoration was affected by root region, type of post and type of cement used.